DEVELOPMENT STUDENT’S WORKSHEET BY INSTILLING MATHEMATICAL CREATIVE THINKING ABILITY ON SETS THEORY STUDENTS GRADE VII - Endang Mulyani; Suparman Suparman (Universitas Ahmad Dahlan, 2020)
This research was aims to know the development procedure, validity, practicality, and effectiveness of the student's worksheet by instilling mathematical creative thinking ability on junior high school student are that meets valid and practical criteria, as well to know the effectiveness of student's worksheet towards student's mathematical creative thinking ability at SMP Muhammadiyah 2 Depok Sleman in the academic year 2019/2020. The types of research that were conducted the development research. The model used in this research was the ADDIE (Analysis, design, development, implementation, evaluation) model. The subject in this research was student's grade VII at SMP Muhammadiyah 2 Depok Sleman, with the subject of the small-scale trials were five students, and the subject of the big-scale trials were 29 students. In this research, the data collection instruments with the validation test questionnaire for material experts and media experts, the student's response questionnaire, and the student's creative thinking test sheet. The data analysis technique used in this research was data analysis of validity, practicality, and effectiveness. The research outcomes based on validation test of student's worksheet include in category valid from validation of material experts with the average percentage of assessment of material expert is 4,1 with valid category ( ) and validation of media experts with percentage average was 3,8 with valid category ( ). While from and student's response questionnaire, the student's worksheet was 3,4 with practical category ( ), and from effectiveness with the percentage of classical learning completeness student was 72,4 with good category ( ). Students' worksheets by instilling mathematical creative thinking ability are valid, practical, and effective in learning.